2007
DOI: 10.2307/4541143
|View full text |Cite
|
Sign up to set email alerts
|

Individual Size Variation and Population Stability in a Seasonal Environment: A Discrete-Time Model and Its Calibration Using Grasshoppers

Abstract: Much recent literature is concerned with how variation among individuals (e.g., variability in their traits and fates) translates into higher-level (i.e., population and community) dynamics. Although several theoretical frameworks have been devised to deal with the effects of individual variation on population dynamics, there are very few reports of empirically based estimates of the sign and magnitude of these effects. Here we describe an analytical model for sizedependent, seasonal life cycles and evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…; González‐Suárez et al . ), although whether greater trait variability increases or reduces risk of extinction appears to be model and context dependent (Filin & Ovadia ).…”
Section: Introductionmentioning
confidence: 99%
“…; González‐Suárez et al . ), although whether greater trait variability increases or reduces risk of extinction appears to be model and context dependent (Filin & Ovadia ).…”
Section: Introductionmentioning
confidence: 99%
“…This stabilizing effect is different from the one attributed to individual variation in demographic traits [e.g. (size‐related) variation in survival and fecundity; Bjørnstad & Hansen, 1994; Grimm & Uchmanski, 2002; Filin & Ovadia, 2007], as it occurs even in the absence of such variation. However, a similarity still exists in the sense that both an initial structure in the population (which can become exaggerated with time) and randomly generated variability in an initially homogeneous population, increase the within‐generation variability in individual fate, but decrease the between‐generation variability in the average fate (see also Uchmanski, 2000).…”
Section: Discussionmentioning
confidence: 66%
“…They showed that initial body-size variation can enhance population stability and persistence, i.e., cause longer extinction times in comparison to homogenous populations. A recent analytical model by Filin & Ovadia (2007) explored the effect of individual size variation on population dynamics and stability in a seasonal environment. The model shows that the effect of size variation on the population net reproductive rate varies in both magnitude and sign, depending on season length.…”
Section: Discussionmentioning
confidence: 99%
“…In the following, we incorporate variation in both mortality and individual size, in a similar manner to Bjørnstad & Hansen (1994), i.e., by using a Taylor expansion. However, we focus here on the effect of variation on within-season survival, rather than on among-season population dynamics and stability (see also Filin & Ovadia 2007). , for the effect of a) initial body size and b) body size variation on herbivore survival.…”
Section: Theoretical Frameworkmentioning
confidence: 99%